(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2014)
In the article the results of effective application of electroexploration (Vertical Elektro Sounding (VES) method) for the study of landslide processes in Urtsadzor–Goravan area (catchment of R. Vedi) are presented, which were intensified especially after the construction of the main channel for irrigation of lands. Surface landslides shifts are installed at depths of 10–12 m and 20–25 m, relief of the landslide surfaces and boundaries of their distribution are mapped. Locations of wells are recommended in connection with the preparation of geotechnical model for calculating the stability of landslide slope.